AN ANALYSIS ON LIFESTYLE COMPONENTS FOUND IN THE GREAT GATSBY NOVEL AND ITS APPLICATION IN TEACHING WRITING OF DESCRIPTIVE TEXT - Juita Triana (p-ISSN 2356-0576, 2022)
Based on a research on Fitzgerald’s novel The Great Gatsby, this writing tries to present some physical aspects of the lifestyle of the characters in the novel. Those are: the style of housing, dressing, fashions of eating, party, and uses time and space, and technology. The research uses descriptive qualitative method. This analysis hopefully will facilitate the English learners to be able to write descriptive text since it can be the inspiration in describing their objects by applying the appropriate rich vocabularies in the interesting language style and ideas organization. Here, the writer also tries to show the possibility of this finding to be an alternative medium supporting a more alive writing class